A conserved KLF-autophagy pathway modulates nematode lifespan and mammalian age-associated vascular dysfunction. Issue 1 (December 2017) - Hsieh, Paishiun; Zhou, Guangjin; Yuan, Yiyuan; Zhang, Rongli; Prosdocimo, Domenick; Sangwung, Panjamaporn; Borton, Anna; Boriushkin, Evgenii; Hamik, Anne; Fujioka, Hisashi; Fealy, Ciaran; Kirwan, John; et al.
Abstract Loss of protein and organelle quality control secondary to reduced autophagy is a hallmark of aging. However, the physiologic and molecular regulation of autophagy in long-lived organisms remains incompletely understood. Here we show that the Kruppel-like family of transcription factors are important regulators of autophagy and healthspan inC. elegans, and also modulate mammalian vascular age-associated phenotypes. Kruppel-like family of transcription factor deficiency attenuates autophagy and lifespan extension across mechanistically distinct longevity nematode models. Conversely, Kruppel-like family of transcription factor overexpression extends nematode lifespan in an autophagy-dependent manner. Furthermore, we show the mammalian vascular factor Kruppel-like family of transcription factor 4 has a conserved role in augmenting autophagy and improving vessel function in aged mice. Kruppel-like family of transcription factor 4 expression also decreases with age in human vascular endothelium. Thus, Kruppel-like family of transcription factors constitute a transcriptional regulatory point for the modulation of autophagy and longevity inC. elegans with conserved effects in the murine vasculature and potential implications for mammalian vascular aging. KLF family transcription factors (KLFs) regulate many cellular processes, including proliferation, survival and stress responses. Here, the authors position KLFs as important regulators of autophagy and lifespan inC. elegans, a role that may extend to the modulation of age-associated vascular phenotypes in mammals.